Analysis of Factors Affecting Women's Participation in IVA (Visual Inspection of Acetic Acid) Examination at the Kebonsari Health Center, Surabaya, Indonesia - Nabila Sukma Tania; Wiwik Afridah; Ika Arifiyanti (HM Publisher, 2023)
Visual inspection of acetic acid (IVA) is a simple method of detecting abnormal cell changes in the cervix (cervix) that may indicate the presence of precancerous lesions or cervical cancer. Factors such as stigmatization, myths or false beliefs associated with the examination, or taboos against examining the female reproductive organs may hinder participation. This study aimed to determine the factors that influence women's participation in VIA examinations at the Kebonsari Health Center, Surabaya, Indonesia. This study was qualitative observational research. Extracting information is done by interviewing research respondents. The results of the in-depth discussion found a number of factors that contributed to the lack of participation in IVA activities at the Kebonsari Health Center, Surabaya, Indonesia. The problem of human resources is a factor that is believed to play a role in the lack of participation of respondents in IVA activities at the Kebonsari Health Center, Surabaya, Indonesia. Respondents complained that they often had difficulty getting VIA examination services due to the absence of implementing staff at the Health Center location. In conclusion, the human resources implementing IVA services and the lack of respondents' knowledge of the IVA program are the main factors in the low participation of women in the IVA program at the Kebonsari Health Center, Surabaya, Indonesia.